Hubungan Karakteristik Individu, Kondisi Pekerjaan Dan Lingkungan Kerja Dengan Stres Kerja Pada Guru Di SDN Meruya Utara 13, Kembangan, Jakarta Barat Tahun 2023 - Syafitri, Dini; Saiful Bahri, Beben; Pramono, Budi; Anastasia Febriani, Susana (BULLET : Jurnal Multidisiplin Ilmu, 2024)
Teachers will spend most of their time at work, namely at school by doing the same tasks every day. Therefore, the condition of the school's physical environment must meet the requirements that aim not to cause teachers to experience work stress. Work stress is a state of tension that causes physical and psychological imbalances, which have an impact on emotions, thought processes, and employee conditions. Job stress in teachers can occur not only from one causal factor, but from a variety of causal factors, both internal and external. This study aims to determine "The Relationship between Individual Characteristics, Working Conditions and Work Environment with Job Stress in Teachers at SDN Meruya Utara 13, Kembangan, West Jakarta in 2023". This study discusses individual characteristics, work conditions, and the physical and social work environment. This study used analytic research with a cross sectional approach. The subjects of this study were teachers at SDN Meruya Utara 13, Kembangan, West Jakarta with a sample size of 24 teachers. Analysis of the data obtained in this study was carried out using the chi square statistical test. The results of univariate analysis showed that 12 teachers (50%) experienced moderate work stress and 12 teachers (50%) experienced severe work stress. Based on the results of bivariate analysis, it is found that the variables associated with work stress in teachers are individual characteristics (age), work conditions (workload and work routine), physical work environment (lighting), and social work environment (interpersonal relationships).